Operational research capacity building through the Structured Operational Research Training Initiative (SORT-IT) in China: implementation, outcomes and challenges - Ning Feng; Jeffrey Karl Edwards; Philip Odhiambo Owiti; Guo-Min Zhang; Zulma Vanessa Rueda Vallejo; Katrina Hann; Shui-Sen Zhou; Myo Minn Oo; Elizabeth Marie Geoffroy; Chao Ma; Tao Li; Jun Feng; et al. (BMC, 2021)
Abstract Background Chinese Center for Disease Control and Prevention (China CDC) introduced the Structured Operational Research Training Initiative (SORT IT) into China to build a special capacity and equip public health professionals with an effective tool to support developing countries in strengthening their operational research. The paper aims to investigate and analyze the implementation, outcomes and challenges of the first cycle of SORT IT in China. Main text As a result of the successful implementation, SORT IT China, Cycle 1 has demonstrated fruitful outputs as exemplified by the 18-month follow-up to the post-training initiatives of the twelve participants, who all achieved the four milestones required by SORT IT. Eleven of twelve (92%) manuscripts generated that focused on the prevention and control of malaria, influenza, HIV/AIDS, hepatitis B, schistosomiasis, tuberculosis and Japanese encephalitis were published by peer-reviewed international journals with the impact factor ranging from 2.6 to 4.8. The most up-to-date citation count on February 19, 2021 was 53 times out of which 31 times were cited by Science Citation Index papers with 94.827 impact factor in total. Six senior professionals from China CDC also facilitated the whole SORT IT training scheme as co-mentors under the guidance of SORT IT mentors. The twelve participants who gained familiarity with the SORT IT courses and training principles are likely become potential mentors for future SORT IT, but they as the non-first language speakers/users of English also faced the challenge in thoroughly understanding the modules delivered in English and writing English academically to draft the manuscripts. Conclusion The outcomes from the first cycle of SORT IT in China have led to studies contributing to narrowing the knowledge gap among numerous public health challenges nationally and internationally. It is believed the researchers who participated will continue to apply the skills learned within their domain and help build the training capacity for future operational research courses both in China and in developing countries with similar needs. Graphic Abstract